Meta‐Analysis of Counseling Outcomes for Youth With Conduct Disorders. (January 2017) - Erford, Bradley T.; Bardhoshi, Gerta; Ross, Margaret; Gunther, Chelsea; Duncan, Kelly
Abstract : Twenty‐one clinical trials were synthesized using a random‐effects model, which substantiated that counseling generally produces a medium effect in treating conduct disorder in youth at termination ( d + = 0.30 to 0.57; k = 28). However, the lasting effects at follow‐up were unclear because few follow‐up studies ( k = 13) have been conducted ( d + = −0.53 to 0.58), and only 2 randomized controlled follow‐up studies were located. No effects of moderating variables were evident. Implications for counseling practice and outcome research are addressed.